Graft-modified ethylene polymer, polyamide composition containing graft-modified ethylene polymer and use thereof

JP7639121B2Active Publication Date: 2025-03-04MITSUI CHEMICALS INC
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2023510297
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-03-29
Filing Date
2022-01-14
Publication Date
2025-03-04
Estimated Expiration
2042-01-14

AI Technical Summary

Benefits of technology

【0010】 本発明のグラフト変性エチレン系重合体(X)は、それ自体、耐衝撃性、柔軟性、流動性に優れる。また、本発明のグラフト変性エチレン系重合体(X)をポリアミドなどのエンジニアリング·プラスチックに添加することにより、エンジニアリング·プラスチックの耐衝撃性、柔軟性、流動性、耐ヒートショック性などの改良効果に優れるので、エンジニアリング·プラスチックの物性改良材に好適に用い得る。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007639121000001
    Figure 0007639121000001
  • Figure 0007639121000002
    Figure 0007639121000002
  • Figure 0007639121000003
    Figure 0007639121000003
Patent Text Reader

Abstract

The purpose of the present invention is to obtain a graft-modified ethylene / α-olefin copolymer that is suitable as an impact resistance improvement material for an engineering plastic such as a polyamide, and to obtain a polyamide composition with improved impact resistance, especially impact resistance at low temperatures. The present invention relates to a graft-modified ethylene polymer (X) that is obtained by using a polar compound to graft-modify an ethylene / α-olefin copolymer (A) satisfying the following requirements (A-i) through (A-iv). (A-i) The included quantity of structural units (a) derived from ethylene is 51-99 mol%, and the included quantity of structural units (b) derived from a C5-20 α-olefin is 1-49 mol% (where the total of the structural units (a) and the structural units (b) is 100 mol%). (A-ii) The density is 0.850-0.875 g / cm3. (A-iii) The melt flow rate (MFR) at 190°C and a load of 2.16 kg is 0.1-25 g / 10 min. (A-iv) The total of vinyl-type double bonds, vinylidene-type double bonds, disubstituted olefin-type double bonds, and trisubstituted olefin-type double bonds is 0.16-1.00 per 1000 carbon atoms as calculated by 1H-NMR.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to a graft-modified ethylene-α-olefin copolymer having excellent impact resistance, a polyamide composition containing the graft-modified ethylene-α-olefin copolymer, and uses thereof. [Background technology]

[0002] Due to its excellent physical properties, polyamide (nylon) is used as an engineering plastic in a variety of electrical and electronic components, machine components, and automotive components. In recent years, molded products for these applications have become thinner, smaller, and more complex in shape, requiring polyamide resins to have an improved balance between mechanical strength such as impact resistance and rigidity and flowability during molding.

[0003] As a method for improving the impact resistance of polyamides, a method has been proposed in which an ethylene-α-olefin copolymer grafted with an α,β-unsaturated carboxylic acid is used as an impact modifier (Patent Document 1). However, with the proposed polyamide composition, attempts to improve impact resistance have been found to tend to result in a decrease in rigidity and fluidity.

[0004] On the other hand, a method of adding a polyhydric alcohol having a melting point of 150 to 200° C. has been proposed as a method for improving the fluidity of polyamide (Patent Document 2). However, there is a concern that the polyhydric alcohol may bleed out onto the surface of the molded article obtained by adding the polyhydric alcohol.

[0005] In addition, Patent Documents 3 and 4 disclose that polyamide compositions excellent in mechanical strength, moldability, and surface appearance can be obtained by using specific diamines as diamine components constituting polyamides, but the effects thereof are still not sufficient.

[0006] Previously proposed ethylene-α-olefin copolymers grafted with α,β-unsaturated carboxylic acids have not yet provided sufficient impact resistance improvement effects for some applications, and there is a need to develop better impact modifiers and polyamide compositions with even better impact resistance. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] Japanese Patent Application Publication No. 2019-35030 [Patent Document 2] Japanese Patent Application Laid-Open No. 2000-345031 [Patent Document 3] Japanese Patent Application Laid-Open No. 2008-095066 [Patent Document 4] Japanese Patent Application Laid-Open No. 2011-148267 Summary of the Invention [Problem to be solved by the invention]

[0008] The object of the present invention is to obtain a graft-modified ethylene-α-olefin copolymer suitable as an impact modifier for engineering plastics such as polyamides, and to obtain a polyamide composition having improved impact resistance, particularly at low temperatures. [Means for solving the problem]

[0009] The present invention relates to a graft-modified ethylene polymer (X) obtained by graft-modifying an ethylene-α-olefin copolymer (A) that satisfies the following requirements (Ai) to (A-iv) with a polar compound. (Ai) The content of the structural unit (a) derived from ethylene is 51 to 9 0 % by mole, and the content of the structural unit (b) derived from an α-olefin having 5 to 20 carbon atoms is 1 0 The range is from 1 to 49 mol % (where the total of the structural units (a) and (b) is 100 mol %). (A-ii) Density: 0.850 to 0.875 g / cm 3 The range is. (A-iii) The melt flow rate (MFR) at 190°C under a load of 2.16 kg is in the range of 0.1 to 25 g / 10 min. (A-iv) 1 The total number of vinyl double bonds, vinylidene double bonds, di-substituted olefin double bonds and tri-substituted olefin double bonds per 1000 carbon atoms as determined by H-NMR is 0.16 to 1.00. [Effects of the Invention]

[0010] The graft-modified ethylene polymer (X) of the present invention is excellent in impact resistance, flexibility, and flowability by itself. Furthermore, by adding the graft-modified ethylene polymer (X) of the present invention to engineering plastics such as polyamides, the impact resistance, flexibility, flowability, heat shock resistance, etc. of the engineering plastics are improved, and the graft-modified ethylene polymer (X) can be suitably used as a property improver for engineering plastics. DETAILED DESCRIPTION OF THE INVENTION

[0011] Ethylene-α-olefin copolymer (A) The ethylene-α-olefin copolymer (A), which is the raw material for the graft-modified ethylene polymer (X) of the present invention, is an ethylene copolymer that satisfies the following requirements (Ai) to (A-iv).

[0012] [Requirements (Ai)] The ethylene-α-olefin copolymer (A) contains a structural unit (a) derived from ethylene and a structural unit (b) derived from an α-olefin having 5 to 20 carbon atoms, and the structural unit (a) accounts for 51 to 9 mole percent of the total of the structural units (a) and (b). 0 % by mole, and the structural unit (b) is 1 0 Contains up to 49 mol%.

[0013] The lower limit of the content of the structural unit (a) relative to the total of 100 mol% of the structural units (a) and (b) is preferably 60 mol%, more preferably 70 mol%, even more preferably 75 mol%, and particularly preferably 80 mol%, and the upper limit of the content of the structural unit (a) is 、9 0 mol% the law of nature , 86 mol% I like Desirable.

[0014] The lower limit of the content of the structural unit (b) relative to the total of 100 mol% of the structural units (a) and (b) is 、1 0 mol% the law of nature , 14 mol% I like Preferably, the upper limit for the content of the structural unit (b) is 40 mol %, more preferably 30 mol %, even more preferably 25 mol %, and particularly preferably 20 mol %.

[0015] When the content of the structural unit (a) derived from ethylene satisfies the above range, the graft-modified ethylene polymer obtained by graft-modifying the ethylene-α-olefin copolymer (A) with a polar compound has excellent impact resistance.

[0016] Specific examples of the α-olefins having 5 to 20 carbon atoms constituting the ethylene-α-olefin copolymer (A) according to the present invention include linear α-olefins having 5 to 20 carbon atoms, such as 1-pentene, 1-hexene, 1-octene, 1-decene, 1-undecene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-octadecene, and 1-eicosene, as well as branched α-olefins having 5 to 20 carbon atoms (preferably 6 to 15 carbon atoms), such as 3-methyl-1-butene, 3-methyl-1-pentene, 4-methyl-1-pentene, 3-ethyl-1-pentene, 4,4-dimethyl-1-pentene, 4-methyl-1-hexene, 4,4-dimethyl-1-hexene, 4-ethyl-1-hexene, and 3-ethyl-1-hexene. Among these α-olefins, α-olefins having 6 to 15 carbon atoms are preferred, α-olefins having 6 to 12 carbon atoms are more preferred, 1-hexene, 1-octene and 1-decene are further preferred, and 1-octene is particularly preferred.

[0017] These α-olefins having 5 to 20 carbon atoms may be one type or two or more types of α-olefins. [Requirement (A-ii)] Density 0.850~0.875g / cm 3 The lower limit of the density is 0.853 g / cm 3 and preferably 0.855 g / cm 3 More preferably, it is 0.858 g / cm 3 The upper limit of the density is more preferably 0.874 g / cm. 3 Preferably, it is 0.872 g / cm 3 More preferably, it is 0.870 g / cm 3 It is more preferable that:

[0018] When the density satisfies the above range, the graft-modified ethylene polymer (X) obtained by graft-modifying the ethylene-α-olefin copolymer (A) with a polar compound has excellent impact resistance.

[0019] [Requirement (A-iii)] The melt flow rate (MFR) at 190°C under a load of 2.16 kg is in the range of 0.1 to 25 g / 10 min. The lower limit of the melt flow rate range is preferably 0.8 g / 10 min, more preferably 0.9 g / 10 min, even more preferably 1.0 g / 10 min, and particularly preferably 1.1 g / 10 min. The upper limit of the melt flow rate range is preferably 22 g / 10 min, more preferably 20 g / 10 min, even more preferably 19 g / 10 min, and particularly preferably 18 g / 10 min.

[0020] When the MFR satisfies the above range, the graft-modified ethylene polymer (X) obtained by graft-modifying the ethylene-α-olefin copolymer (A) with a polar compound has excellent impact resistance.

[0021] [Requirement (A-iv)] 1 The sum of the vinyl double bonds, vinylidene double bonds, di-substituted olefin double bonds, and tri-substituted olefin double bonds described below per 1000 carbon atoms (1000C) determined by H-NMR (hereinafter, sometimes referred to as the total double bond amount) is in the range of 0.16 to 1.00 / 1000C. The lower limit of the total double bond amount is preferably 0.18 / 1000C, more preferably 0.19 / 1000C, even more preferably 0.20 / 1000C, and particularly preferably 0.22 / 1000C. The upper limit of the total double bond amount is preferably 0.95 / 1000C, more preferably 0.90 / 1000C, even more preferably 0.85 / 1000C, and particularly preferably 0.80 / 1000C.

[0022] [ka] In each formula, * indicates a bond to an atom other than a hydrogen atom.

[0023] <Double bond amount (unsaturated bond amount)> The amount of double bonds in ethylene-α-olefin copolymer (A) was determined by 1 H-NMR measurements were performed using a JEOL ECX400P nuclear magnetic resonance spectrometer. Signals derived from double bonds were observed, including vinyl double bonds (vinyl groups), vinylidene double bonds (vinylidene groups), di-substituted olefin double bonds, and tri-substituted olefin double bonds. The amount of double bonds was quantified from the integrated intensity of each signal. The main-chain methylene signal of ethylene-α-olefin copolymer (A) was used as the chemical shift reference (1.2 ppm). The total amount of vinyl and vinylidene groups was calculated as the amount of terminal double bonds, and the total amount of di- and tri-substituted olefin double bonds was calculated as the amount of internal unsaturated bonds. The total amount of double bonds (total double bond amount) was calculated as the sum of the individual double bonds. Analysis was performed with a quantitation limit of 0.1 / 1000C. If signals were observed even when the number of double bonds was less than 0.1 / 1000C, the calibration curve was extrapolated to calculate the amount of double bonds.

[0024] The peaks of the hydrogen atoms a to e are observed near the following positions. Hydrogen atom a peak: 4.60 ppm Hydrogen atom b peak: 4.85 ppm Hydrogen atom c peak: 5.10 ppm Hydrogen atom d peak: 5.25 ppm Hydrogen atom e peak: 5.70 ppm The quantitative formula for the amount of double bonds is as follows: Amount of vinyl double bonds = {(integrated intensity of signal b) + (integrated intensity of signal e)} / 3 Amount of vinylidene double bonds = (integral intensity of signal a) / 2 Amount of disubstituted olefinic double bonds = (integral intensity of signal d) / 2 Amount of trisubstituted olefinic double bonds = (integrated intensity of signal c) Total double bonds contained in ethylene-α-olefin copolymer amountWhen the total double bond content of an ethylene-α-olefin copolymer is less than 0.16 / 1000C, the molecular weight of the graft-modified ethylene polymer obtained by graft-modifying with a polar compound is significantly reduced, whereas when the total double bond content of the ethylene-α-olefin copolymer is within the range of the present invention, i.e., 0.16 to 1.00 / 1000C, the reduction in the molecular weight of the graft-modified ethylene polymer is suppressed, which is effective in improving impact resistance. On the other hand, when the total double bond content exceeds the above range, the molecular weight of the graft-modified ethylene polymer increases, and when it is blended with a polyamide, the flowability of the resulting composition may decrease.

[0025] <Graft-modified ethylene polymer (X)> One embodiment of the graft-modified ethylene polymer (X) of the present invention is a graft-modified ethylene polymer obtained by graft-modifying the above-mentioned ethylene-α-olefin copolymer (A) with a polar compound, and preferably satisfies the following requirements (Xi) and (X-ii):

[0026] [Requirements (Xi)] MFR 10 / MFR 2.16 is 10 or more, preferably 10 to 20, more preferably 10 to 15, and even more preferably 10 to 12.5 (however, MFR 10 is the melt flow rate measured at 190°C under a 10 kg load according to the ASTM D1238 method, and MFR 2.16 MFR is the melt flow rate measured at 190°C under a load of 2.16 kg according to the method of ASTM D1238. 10 / MFR 2.16 is a value that is considered to be one of the indicators of the degree of long chain branching of a polymer, and MFR 10 / MFR 2.16 A small MFR indicates less long chain branching. 10 / MFR 2.16 When the value is 10 or more, the impact resistance and fluidity are excellent.

[0027] MFR 10 / MFR 2.16Although the reason is unclear, it is thought that a graft-modified ethylene polymer having a viscosity of less than 10 has a high viscosity under high shear stress when kneaded with polyamide, which deteriorates the dispersibility of the polymer in the polyamide, resulting in a decrease in impact resistance.

[0028] On the other hand, MFR 10 / MFR 2.16 A polymer having a molecular weight of more than 20 may have a reduced mechanical strength and impact resistance. [Requirement (X-ii)] The graft amount of the polar compound is 0.1 to 5% by mass. Here, the lower limit of the graft amount of the polar compound is preferably 0.3% by mass, more preferably 0.55% by mass, even more preferably 0.6% by mass, and particularly preferably 0.8% by mass. On the other hand, the upper limit of the graft amount of the polar compound is preferably 4% by mass, more preferably 3% by mass, even more preferably 2% by mass, and particularly preferably 1.7% by mass.

[0029] A graft-modified ethylene polymer having a graft amount of the polar compound less than the above lower limit may have reduced compatibility with polyamide, resulting in a composition with reduced impact resistance. On the other hand, a graft-modified ethylene polymer having a graft amount exceeding the above upper limit may have an excessively strong interaction with polyamide, resulting in a composition with reduced fluidity.

[0030] The polar compound to be graft-modified onto the ethylene-α-olefin copolymer (A) according to the present invention is at least one polar compound selected from the group consisting of hydroxyl group-containing ethylenically unsaturated compounds, amino group-containing ethylenically unsaturated compounds, epoxy group-containing ethylenically unsaturated compounds, aromatic vinyl compounds, unsaturated carboxylic acids and derivatives thereof, vinyl ester compounds, and vinyl chloride.

[0031] Among these polar compounds, unsaturated carboxylic acids and derivatives thereof are preferred, and examples of these unsaturated carboxylic acids and derivatives thereof include unsaturated carboxylic acids having 3 to 10 carbon atoms, preferably 3 to 8 carbon atoms, and derivatives of the unsaturated carboxylic acids. Examples of derivatives of unsaturated carboxylic acids include acid anhydrides, esters, amides, and imides of unsaturated carboxylic acids.

[0032] Examples of the unsaturated carboxylic acid include monobasic acids such as acrylic acid and methacrylic acid; and dibasic acids such as maleic acid, fumaric acid, itaconic acid, citraconic acid, and 5-norbornene-2,3-dicarboxylic acid.

[0033] Examples of the acid anhydrides of unsaturated carboxylic acids include acid anhydrides of dibasic acids such as maleic acid, itaconic acid, citraconic acid, and 5-norbornene-2,3-dicarboxylic acid.

[0034] Examples of the esters of unsaturated carboxylic acids include esters and half esters of methyl acrylate, methyl methacrylate, ethyl acrylate, ethyl methacrylate, glycidyl acrylate, monoethyl maleate, diethyl maleate, monomethyl fumarate, dimethyl fumarate, monomethyl itaconic acid, diethyl itaconic acid, and the like.

[0035] Examples of the amide of the unsaturated carboxylic acid include acrylamide, methacrylamide, maleic acid monoamide, maleic acid diamide, maleic acid-N-monoethylamide, maleic acid-N,N-diethylamide, maleic acid-N-monobutylamide, maleic acid-N,N-dibutylamide, fumaric acid monoamide, fumaric acid diamide, fumaric acid-N-monobutylamide, and fumaric acid-N,N-dibutylamide.

[0036] Examples of the imide of the unsaturated carboxylic acid include maleimide, N-butylmaleimide, and N-phenylmaleimide. One embodiment of the graft-modified ethylene polymer (X) of the present invention is preferably a maleic anhydride-grafted ethylene-1-octene copolymer that satisfies the above requirement (Xi) and the following requirements (X-iii) to (X-vi).

[0037] [Requirement (X-iii)] The graft amount of maleic anhydride is in the range of 0.1 to 3 mass %. Here, the lower limit of the graft amount of maleic anhydride is preferably 0.4 mass %, more preferably 0.55 mass %, and even more preferably 0.6 mass %. On the other hand, the upper limit of the graft amount of maleic anhydride is is 2 It must be mass% I like Desirable.

[0038] [Requirement (X-iv)] The graft-modified ethylene polymer (X) contains a structural unit (a) derived from ethylene and a structural unit (b) derived from an α-olefin having 5 to 20 carbon atoms, and the structural unit (a) accounts for 51 to 9 mole percent of the total of the structural units (a) and (b). 0 % by mole, and the structural unit (b) is 1 0 Contains up to 49 mol%.

[0039] The lower limit of the content of the structural unit (a) relative to the total of 100 mol% of the structural units (a) and (b) is preferably 60 mol%, more preferably 70 mol%, even more preferably 75 mol%, and particularly preferably 80 mol%, and the upper limit of the content of the structural unit (a) is 、9 0 mol% the law of nature , 86 mol% I like Desirable.

[0040] The lower limit of the content of the structural unit (b) relative to the total of 100 mol% of the structural units (a) and (b) is 、1 0 mol% the law of nature , 14 mol% I likePreferably, the upper limit for the content of the structural unit (b) is 40 mol %, more preferably 30 mol %, even more preferably 25 mol %, and particularly preferably 20 mol %.

[0041] [Requirements (Xv)] Density: 0.850~0.880g / cm 3 The lower limit of the density is 0.853 g / cm 3 and preferably 0.855 g / cm 3 More preferably, it is 0.858 g / cm 3 The upper limit of the density is more preferably 0.877 g / cm. 3 Preferably, it is 0.865 g / cm 3 More preferably, it is 0.874 g / cm 3 It is more preferable that:

[0042] [Requirements (X-vi)] The melt flow rate (MFR) at 190°C under a load of 2.16 kg is in the range of 0.1 to 25 g / 10 min. The lower limit of the melt flow rate range is preferably 0.2 g / 10 min, more preferably 0.3 g / 10 min, even more preferably 0.35 g / 10 min, and particularly preferably 0.4 g / 10 min. The upper limit of the melt flow rate range is preferably 22 g / 10 min, more preferably 20 g / 10 min, even more preferably 15 g / 10 min, and particularly preferably 10 g / 10 min.

[0043] <Method for producing graft-modified ethylene polymer (X)> The graft-modified ethylene polymer of the present invention can be produced by grafting a polar compound onto the ethylene-α-olefin copolymer (A) by any of various known methods.

[0044] Specifically, for example, the ethylene-α-olefin copolymer (A) is dissolved in an organic solvent, and then a polar compound such as an unsaturated carboxylic acid or a derivative thereof, and optionally a radical initiator such as an organic peroxide, are added to the resulting solution, and the reaction is carried out usually at a temperature of 60 to 350°C, preferably 80 to 190°C, for 0.5 to 15 hours, preferably 1 to 10 hours. Alternatively, the ethylene-α-olefin copolymer (A) is added to an extruder or the like without a solvent, and optionally a radical initiator such as an unsaturated carboxylic acid or a derivative thereof, and the reaction is carried out usually at a temperature equal to or higher than the melting point of the ethylene-α-olefin copolymer (A), preferably 160 to 350°C, for 0.5 to 10 minutes.

[0045] The amount of graft modification of the ethylene-α-olefin copolymer (A) was determined by measuring the amount of structural units derived from polar compounds such as unsaturated carboxylic acids or their derivatives (graft modification amount) using an infrared absorption analyzer, based on the peak derived from the structural units (1790 cm when maleic anhydride was used). -1 The intensity of the chromatogram was measured and quantified using a calibration curve prepared in advance.

[0046] The graft-modified ethylene polymer (X) of the present invention may contain, as necessary, other additives such as a heat stabilizer, a weather stabilizer, a light stabilizer, an antioxidant, an antioxidant, a fatty acid metal salt, a softener, a dispersant, a colorant, a pigment, an ultraviolet absorber, and a nucleating agent, within the range that does not impair the object of the present invention.

[0047] <Application> The graft-modified ethylene polymer (X) of the present invention is excellent in impact resistance, flexibility, and fluidity by itself, and when added to engineering plastics such as polyamides, it has excellent effects of improving the impact resistance, flexibility, fluidity, heat shock resistance, etc. of the engineering plastics, and therefore can be suitably used as a property improver for engineering plastics.

[0048] <Polyamide (P)> The polyamide (P) according to the present invention is not particularly limited, and various polyamides (also called nylons), such as conventionally known aliphatic polyamides, semi-aromatic polyamides, and aromatic polyamides, can be used without limitation as long as the effects of the present invention are not impaired. For example, a melt-moldable polyamide obtained by polycondensation reaction of lactam or diamine with dicarboxylic acid can be used. Specific examples of the polyamide (P) include the following polymers: (1) Polycondensates of organic dicarboxylic acids having 4 to 12 carbon atoms and organic diamines having 2 to 13 carbon atoms, such as polyhexamethylene adipamide [6,6 nylon], which is a polycondensate of hexamethylene diamine and adipic acid, polyhexamethylene azelamide [6,9 nylon], which is a polycondensate of hexamethylene diamine and azelaic acid, and polyhexamethylene sebacamide [6, 10 nylon], polyhexamethylene dodecanoamide [6,12 nylon], which is a polycondensation product of hexamethylenediamine and dodecanedioic acid, semi-aromatic polyamides (PA6T, PA9T, PA10T, PA11T), which are polycondensation products of aromatic dicarboxylic acids and aliphatic diamines, and polybis(4-aminocyclohexyl)methanedodecane, which is a polycondensation product of bis-p-aminocyclohexylmethane and dodecanedioic acid.

[0049] Examples of the organic dicarboxylic acids include adipic acid, pimelic acid, suberic acid, phthalic acid, terephthalic acid, isophthalic acid, naphthalenedicarboxylic acid, phenylenedioxydiacetic acid, oxydibenzoic acid, diphenylmethanedicarboxylic acid, diphenylsulfonedicarboxylic acid, biphenyldicarboxylic acid, sebacic acid, dodecane diamine, etc. Examples of the organic diamines include hexamethylenediamine, octamethylenediamine, nonanediamine, octanediamine, decanediamine, undecanediamine, dodecanediamine, etc. (2) Polycondensation products of ω-amino acids, such as polyundecaneamide [11 nylon], which is a polycondensation product of ω-aminoundecanoic acid. (3) Ring-opening polymers of lactams, such as polycapramide [nylon 6], which is a ring-opening polymer of ε-caprolactam, and polylaurinlactam [nylon 12], which is a ring-opening polymer of ω-laurolactam.

[0050] Among the polyamides (P) exemplified above, aliphatic polyamides are preferred, polyhexamethylene adipamide [6,6 nylon], polyhexamethylene azelamide [6,9 nylon], polycapramide [6 nylon], and polylaurin lactam [12 nylon] are more preferred, and polyhexamethylene adipamide [6,6 nylon] and polycapramide [6 nylon] are even more preferred.

[0051] The melting point of the polyamide (P) is preferably 150° C. to 330° C., more preferably 150 to 270° C. A melting point of not more than the upper limit is preferred in that decomposition and volatilization of the graft-modified ethylene polymer are suppressed during molding. A melting point of not less than the lower limit is preferred in that the impact strength of the resulting polyamide composition is high.

[0052] In addition, in the present invention, as the polyamide (P), for example, a polyamide produced from adipic acid, isophthalic acid, and hexamethylenediamine can be used, and further, a blend of two or more polyamides, such as a mixture of nylon 6 and nylon 6,6, can also be used.

[0053] <Polyamide composition> The polyamide composition of the present invention contains 50 to 99% by mass of the polyamide (P) and 1 to 50% by mass of the modified ethylene polymer (X) (wherein the total of the polyamide (P) and the graft-modified ethylene polymer (X) is 100% by mass).

[0054] From the viewpoint of more suitably achieving the effects of the present invention, the lower limit of the content of polyamide (P) is preferably 60% by mass or more, more preferably 70% by mass or more, and even more preferably 80% by mass or more, and the upper limit is preferably 95% by mass or less, more preferably 93% by mass or less, and even more preferably 90% by mass or less.

[0055] On the other hand, the lower limit of the content of the modified ethylene polymer (X) is preferably 5% by mass or more, more preferably 7% by mass or more, and even more preferably 10% by mass or more, and the upper limit is preferably 40% by mass or less, more preferably 30% by mass or less, and even more preferably 20% by mass or less.

[0056] When the polyamide composition of the present invention contains the modified ethylene polymer (X) in the above range, it is possible to obtain a molded article having excellent impact resistance, particularly low-temperature impact resistance, and flowability.

[0057] In addition to the polyamide (P) and the graft-modified ethylene polymer (X), the polyamide composition of the present invention may contain, as necessary, additives such as other synthetic resins, other rubbers, antioxidants, heat stabilizers, weather stabilizers, slip agents, antiblocking agents, crystal nucleating agents, pigments, hydrochloric acid absorbers, and copper inhibitors in an amount of usually 0.01 to 10 parts by mass, and preferably 0.1 to 5 parts by mass per 100 parts by mass of the polyamide composition, within a range that does not impair the object of the present invention.

[0058] [Filler] The polyamide composition of the present invention may also be a filler-containing polyamide composition further containing typically 1 to 100 parts by mass, preferably 5 to 80 parts by mass, and more preferably 10 to 70 parts by mass of a filler per 100 parts by mass of the polyamide composition. Such a filler-containing polyamide composition is useful when it is desired to further improve the mechanical strength of a molded article, or when a molded article having an adjusted linear expansion coefficient (mold shrinkage rate) is required.

[0059] Examples of fillers include fibrous fillers, granular fillers, and plate-like fillers. Specific examples of fibrous fillers include glass fiber, carbon fiber, and aramid fiber. A suitable example of glass fiber is chopped strands with an average fiber diameter of 6 to 14 μm. Specific examples of granular or plate-like fillers include calcium carbonate, mica, glass flakes, glass balloons, magnesium carbonate, silica, talc, clay, and pulverized carbon fiber or aramid fiber. Note that these fillers are not included in the above-mentioned additives.

[0060] <Method for producing polyamide composition> The polyamide composition of the present invention can be prepared, for example, by melt-kneading the polyamide (P) and graft-modified ethylene polymer (X), along with optional additives, using various conventional methods. Specifically, the components are simultaneously or sequentially charged into, for example, a Henschel mixer, V-blender, tumbler mixer, ribbon blender, or the like, and then melt-kneaded using a single-screw extruder, multi-screw extruder, kneader, Banbury mixer, or the like. In particular, the use of a device with excellent kneading performance, such as a multi-screw extruder, kneader, or Banbury mixer, can result in a high-quality polyamide composition in which the components are more uniformly dispersed. Furthermore, other additives, such as antioxidants, can be added at any of these stages, as needed.

[0061] [Molded body] The polyamide composition and filler-containing polyamide composition of the present invention can be molded into various molded articles by known molding methods such as injection molding, extrusion molding, inflation molding, blow molding, extrusion blow molding, injection blow molding, press molding, vacuum molding, calendar molding, and foam molding, and can be used in a variety of known applications. [Example]

[0062] The present invention will be described in more detail below with reference to examples, although the present invention is not limited to these examples. The polymers used in the examples and comparative examples are shown below.

[0063] [Ethylene-1-octene copolymer (A)] The ethylene-1-octene copolymer (A) used was the ethylene-1-octene copolymer produced in the following Production Example.

[0064] [Manufacturing Example 1] <Production of ethylene-1-octene copolymer (A-1)> A hexane solution of triisobutylaluminum as a cocatalyst was supplied to one supply port of a 50 L continuous polymerization reactor equipped with a stirring blade at a rate of 20 mmol / hr, a hexane solution of [bis(4-methoxyphenyl)methylene(η5-cyclopentadienyl)(η5-tetramethyloctahydrodibenzofluorenyl)]hafnium dichloride as a main catalyst at a rate of 0.0075 mmol / hr, and a hexane slurry solution of triphenylcarbenium tetrakis(pentafluorophenyl)borate at a rate of 0.034 mmol / hr. Dehydrated and purified normal hexane was continuously supplied so that the total amount of the catalyst solution and the dehydrated and purified normal hexane used as a polymerization solvent was 37.3 L / hr.

[0065] At the same time, ethylene was continuously fed at a rate of 6.4 kg / hr, 1-octene at 7.2 kg / hr, and hydrogen at 110 NL / hr into another feed port of the polymerization reactor, and continuous solution polymerization was carried out under the conditions of a polymerization temperature of 130°C, a total pressure of 2.5 MPaG, and a residence time of 0.5 hours. The n-hexane / toluene mixed solution of ethylene-1-octene copolymer produced in the polymerization reactor was continuously discharged through an outlet at the bottom of the polymerization reactor, and the jacket pressure was adjusted to 3 kg / cm so that the n-hexane / toluene mixed solution of ethylene-1-octene copolymer was maintained at 150°C. 2The mixture was then introduced into a steam-heated connecting pipe. Just before the connecting pipe, a feed port for methanol, a catalyst deactivator, was installed. Methanol was injected at a rate of approximately 11 L / hr and mixed with the ethylene-1-octene copolymer n-hexane / toluene mixed solution. The ethylene-1-octene copolymer n-hexane / toluene mixed solution, maintained at approximately 200°C in the steam-jacketed connecting pipe, was continuously transferred to the flash vessel by adjusting the valve position of the pressure control valve at the end of the connecting pipe to maintain a pressure of approximately 2.5 MPaG. During transfer to the flash vessel, the solution temperature and the valve position were adjusted to maintain a pressure of approximately 0.05 MPaG and a vapor temperature of approximately 200°C. The mixture was then passed through a single-screw extruder with a die temperature set to 190°C. The strands were cooled in a water bath and cut with a pellet cutter to obtain ethylene-1-octene copolymer pellets. The yield was 7.3 kg / 2 hr.

[0066] The physical properties of the ethylene-1-octene copolymer (A-1) obtained above were measured by the methods described below. The measurement results are shown in Table 1. [Manufacturing Example 2] <Production of ethylene-1-octene copolymer (A-2)> In the same manner as in Production Example 1, the amount of 1-octene fed, the polymerization temperature, and the polymerization pressure were adjusted to produce 1-octene copolymer (A-2). The physical properties of the resulting ethylene-1-octene copolymer (A-2) were measured by the methods described below. The measurement results are shown in Table 1.

[0067] [Ethylene-1-octene copolymer (C)] In the comparative examples, the following ethylene-1-octene copolymer (C) was used. (1) As the ethylene-1-octene copolymer (C-1), ENGAGE 8842 manufactured by Dow Chemical was used. (2) As the ethylene-1-octene copolymer (C-2), ENGAGE 8137 manufactured by Dow Chemical was used. (3) The ethylene-1-octene copolymer (C-3) used was ENGAGE 8200, manufactured by Dow Chemical. (4) As the ethylene-1-octene copolymer (C-4), ENGAGE 8100 manufactured by Dow Chemical was used.

[0068] Example 1 <Production of Graft-Modified Ethylene-1-Octene Copolymer (X-1)> An extruder TEX30 (manufactured by The Japan Steel Works, Ltd.) was charged with 100 parts by mass of ethylene-1-octene copolymer (A-1), 1.2 parts by mass of maleic anhydride, and 0.06 parts by mass of Perhexa 25B (2,5-dimethyl-2,5-di(t-butylperoxy)hexane, manufactured by NOF Corporation; decomposition temperature with a half-life of 1 minute: 179.8°C) and operated under the following conditions to obtain a graft-modified ethylene-1-octene copolymer (X-1). The density, maleic anhydride graft amount (modification amount), and MFR of the resulting polymer were measured; the results are shown in Table 1.

[0069] Extruder operating conditions Cylinder temperatures C2 / C3 / C4 / C5 / C6=50℃ / 170℃ / 200℃ / 200℃ / 200℃ Screw rotation speed: 240 rpm Feeder rotation speed: 65 rpm Example 2 <Production of Graft-Modified Ethylene-1-Octene Copolymer (X-2)> A graft-modified ethylene-1-octene copolymer (X-2) was obtained in the same manner as in Example 1, except that the ethylene-1-octene copolymer (A-2) obtained in Production Example 2 was used instead of the ethylene-1-octene copolymer (A-1) used in Example 1. The density, maleic anhydride graft amount (modification amount), and MFR of the obtained polymer were measured, and the results are shown in Table 1.

[0070] Example 3 <Production of Graft-Modified Ethylene-1-Octene Copolymer (X-3)> A graft-modified ethylene-1-octene copolymer (X-3) was obtained in the same manner as in Example 1, except that an ethylene-1-octene copolymer (A-3) (manufactured by Mitsui Chemicals, trade name: Tafmer H-5030S) was used instead of the ethylene-1-octene copolymer (A-1) used in Example 1. The density, maleic anhydride graft amount (modification amount), and MFR of the obtained polymer were measured, and the results are shown in Table 1.

[0071] Example 4 <Production of Graft-Modified Ethylene-1-Octene Copolymer (X-4)> A graft-modified ethylene-1-octene copolymer (X-4) was obtained in the same manner as in Example 1, except that ethylene-1-octene copolymer (A-4) (manufactured by Mitsui Chemicals, product name: Tafmer H-1030S) was used instead of the ethylene-1-octene copolymer (A-1) used in Example 1. The density, maleic anhydride graft amount (modification amount), and MFR of the obtained polymer were measured, and the results are shown in Table 1.

[0072] Comparative Example 1 <Production of Graft-Modified Ethylene-1-Octene Copolymer (Y-1)> A graft-modified ethylene-1-octene copolymer (Y-1) was obtained in the same manner as in Example 1, except that the ethylene-1-octene copolymer (C-1) was used instead of the ethylene-1-octene copolymer (A-1) used in Example 1. The density, maleic anhydride graft amount (modification amount), and MFR of the obtained polymer were measured, and the results are shown in Table 1.

[0073] Comparative Example 2 <Production of Graft-Modified Ethylene-1-Octene Copolymer (Y-2)> A graft-modified ethylene-1-octene copolymer (Y-2) was obtained in the same manner as in Example 1, except that the ethylene-1-octene copolymer (C-2) was used instead of the ethylene-1-octene copolymer (A-1) used in Example 1. The density, maleic anhydride graft amount (modification amount), and MFR of the obtained polymer were measured, and the results are shown in Table 1.

[0074] Comparative Example 3 <Production of Graft-Modified Ethylene-1-Octene Copolymer (Y-3)> A graft-modified ethylene-1-octene copolymer (Y-3) was obtained in the same manner as in Example 1, except that the ethylene-1-octene copolymer (C-3) was used instead of the ethylene-1-octene copolymer (A-1) used in Example 1. The density, maleic anhydride graft amount (modification amount), and MFR of the obtained polymer were measured, and the results are shown in Table 1.

[0075] Comparative Example 4 <Production of Graft-Modified Ethylene-1-Octene Copolymer (Y-4)> A graft-modified ethylene-1-octene copolymer (Y-4) was obtained in the same manner as in Example 1, except that the ethylene-1-octene copolymer (C-4) was used instead of the ethylene-1-octene copolymer (A-1) used in Example 1. The density, maleic anhydride graft amount (modification amount), and MFR of the obtained polymer were measured, and the results are shown in Table 1.

[0076] The physical properties of the polymers obtained in the examples and comparative examples were measured by the following methods. 〔density〕 Density (g / cm 3 ) was determined at 23°C according to ASTM D1505.

[0077] [Melt flow rate (MFR)] The melt flow rate (MFR) was measured in accordance with ASTM D1238 under the conditions of 190°C, 2.16 kg load and 190°C, 10 kg load.

[0078] [Maleic anhydride graft amount] The amount of maleic anhydride grafted was measured by the method described above. [Double bond amount (unsaturated bond amount)] The amount of double bonds was determined by the method described above.

[0079] [Table 1] Example 5 A dry blend of 90 parts by mass of 6,6 nylon (Amilan CM3007, manufactured by Toray Industries, Inc.; melting point: 265°C) and 10 parts by mass of the graft-modified ethylene-1-octene copolymer (X-1) obtained in Example 1 was prepared as polyamide (P-1) using a Henschel mixer. This dry blend was then fed into a twin-screw extruder set at 290°C to prepare pellets of a polyamide composition. The resulting pellets of the polyamide composition were dried overnight at 80°C and then injection-molded under the following conditions to prepare test pieces for physical property testing. The results are shown in Table 2.

[0080] (Injection molding conditions) Cylinder temperature: 280℃ Injection pressure: 40MPa Mold temperature: 80℃ The physical properties of the obtained test pieces for physical property testing and the polyamide compositions were evaluated.

[0081] [Charpy impact test] The notched Charpy impact strength was measured under the following conditions in accordance with JIS K7111.

[0082] <Test conditions> Temperature: 23°C and -40°C Test piece: 10mm (width) x 80mm (length) x 4mm (thickness) [Fluidity (Spiral Flow)] The material was injection molded into a mold with a 3.8 mmφ semicircular spiral groove using an injection molding machine with a cylinder temperature of 280°C, injection pressure of 100 MPa, mold temperature of 80°C, and a clamping force of 50 tonnes, and the flow distance was measured.

[0083] Example 6 Pellets of a polyamide composition were prepared in the same manner as in Example 5, except that the graft-modified ethylene-1-octene copolymer (X-1) was replaced with the graft-modified ethylene-1-octene copolymer (X-2), and test pieces for physical property testing were fabricated. The results are shown in Table 2.

[0084] Example 7 Pellets of a polyamide composition were prepared in the same manner as in Example 5, except that the graft-modified ethylene-1-octene copolymer (X-1) was replaced with the graft-modified ethylene-1-octene copolymer (X-3), and test pieces for physical property testing were fabricated. The results are shown in Table 2.

[0085] Example 8 Pellets of a polyamide composition were prepared in the same manner as in Example 5, except that the graft-modified ethylene-1-octene copolymer (X-1) was replaced with the graft-modified ethylene-1-octene copolymer (X-4), and test pieces for physical property testing were fabricated. The results are shown in Table 2.

[0086] Example 9 A dry blend of polyamide composition was prepared in the same manner as in Example 5, except that nylon 6 (Amilan CM1007, manufactured by Toray Industries, Inc.; melting point: 225°C) was used as polyamide (P-2). This dry blend was then fed into a twin-screw extruder set at 245°C to prepare pellets of the polyamide composition. The resulting pellets of polyamide composition were dried overnight at 80°C and then injection-molded under the following conditions to prepare test pieces for physical property testing. The results are shown in Table 2.

[0087] (Injection molding conditions) Cylinder temperature: 245℃ Injection pressure: 40MPa Mold temperature: 80℃ [Fluidity (Spiral Flow)] The material was injection molded into a mold with a 3.8 mmφ semicircular spiral groove using an injection molding machine with a cylinder temperature of 245°C, injection pressure of 100 MPa, mold temperature of 80°C, and a clamping force of 50 tonnes, and the flow distance was measured.

[0088] Comparative Example 5 Pellets of a polyamide composition were prepared in the same manner as in Example 5, except that the graft-modified ethylene-1-octene copolymer (X-1) was replaced with the graft-modified ethylene-1-octene copolymer (Y-1), and test pieces for physical property testing were fabricated. The results are shown in Table 2.

[0089] Comparative Example 6 Pellets of a polyamide composition were prepared in the same manner as in Example 5, except that the graft-modified ethylene-1-octene copolymer (X-1) was replaced with the graft-modified ethylene-1-octene copolymer (Y-2), and test pieces for physical property testing were fabricated. The results are shown in Table 2.

[0090] Comparative Example 7 Pellets of a polyamide composition were prepared in the same manner as in Example 5, except that the graft-modified ethylene-1-octene copolymer (X-1) was replaced with the graft-modified ethylene-1-octene copolymer (Y-3), and test pieces for physical property testing were fabricated. The results are shown in Table 2.

[0091] Comparative Example 8 Pellets of a polyamide composition were prepared in the same manner as in Example 5, except that the graft-modified ethylene-1-octene copolymer (X-1) was replaced with the graft-modified ethylene-1-octene copolymer (Y-4), and test pieces for physical property testing were fabricated. The results are shown in Table 2.

[0092] Comparative Example 9 Pellets of a polyamide composition were prepared in the same manner as in Example 9, except that the graft-modified ethylene-1-octene copolymer (X-1) was replaced with the graft-modified ethylene-1-octene copolymer (Y-1), and test pieces for physical property testing were fabricated. The results are shown in Table 2.

[0093] Comparative Example 10 Pellets of the polyamide composition were prepared in the same manner as in Example 5, except that the graft-modified ethylene-1-octene copolymer (X-1) was not used, and test pieces for physical property testing were fabricated. The results are shown in Table 2.

[0094] Comparative Example 11 Pellets of the polyamide composition were prepared in the same manner as in Example 9, except that the graft-modified ethylene-1-octene copolymer (X-1) was not used, and test pieces for physical property testing were fabricated. The results are shown in Table 2.

[0095] [Table 2]

Claims

1. A composition comprising a polyamide (P) in the range of 50 to 99 mass %, and a graft-modified ethylene polymer (X) obtained by graft-modifying an ethylene / α-olefin copolymer (A) satisfying the following requirements (A-i) to (A-iv) with at least one polar compound selected from unsaturated carboxylic acids and derivatives thereof, and a graft-modified ethylene polymer selected from maleic anhydride-grafted ethylene / 1-octene copolymer, the graft-modified ethylene polymer (X) further satisfying the following requirements (X-i) and (X-iii) to (X-vi), in an amount in the range of 1 to 50 mass % (wherein the total of the polyamide (P) and the graft-modified ethylene polymer (X) or the maleic anhydride-grafted ethylene / 1-octene copolymer is taken as 100 mass %). Including, A polyamide composition comprising no cellulose nanofibers. (A-i) The content of structural units (a) derived from ethylene is 51 to 90 mol %, and the content of structural units (b) derived from an α-olefin having 5 to 20 carbon atoms is in the range of 10 to 49 mol % (wherein the total of structural units (a) and structural units (b) is 100 mol %). (A-ii) density is 0.850 to 0.875 g / cm 3 The range is. (A-iii) The melt flow rate (MFR) at 190° C. under a load of 2.16 kg is in the range of 0.1 to 25 g / 10 min. (A-iv) 1 The total number of vinyl double bonds, vinylidene double bonds, di-substituted olefin double bonds and tri-substituted olefin double bonds per 1,000 carbon atoms as determined by H-NMR is 0.16 to 1.

00. (Xi) MFR 10 / MFR 2.16 is 10 or more (wherein MFR 10 is the melt flow rate measured at 190° C. under a load of 10 kg according to the method of ASTM D1238, and MFR 2.16 is the melt flow rate measured at 190° C. under a load of 2.16 kg according to the method of ASTM D1238). (X-iii) The graft amount of maleic anhydride is in the range of 0.1 to 3 mass %. (X-iv) The content of structural units (a) derived from ethylene is 51 to 90 mol %, and the content of structural units (b) derived from 1-octene is in the range of 10 to 49 mol % (wherein the total of structural units (a) and structural units (b) is 100 mol %). (Xv) The density is in the range of 0.860 to 0.880 g / cm 3 . (X-vi) The melt flow rate (MFR) at 190° C. under a load of 2.16 kg is in the range of 0.1 to 25 g / 10 min.

2. 2. A polyamide composition comprising the graft-modified ethylene polymer (X) according to claim 1, wherein the ethylene / α-olefin copolymer (A) is an ethylene / 1-octene copolymer.

3. The polyamide composition comprising the graft-modified ethylene polymer (X) according to claim 1, characterized in that the graft-modified ethylene polymer (X) satisfies the requirements (X-i) and (X-ii). (X-i) MFR 10 / M.F.R. 2.16 is 10 or more (however, MFR 10 is the melt flow rate measured at 190°C under a load of 10 kg according to the method of ASTM D1238, and MFR 2.16 is the melt flow rate measured at 190°C under a load of 2.16 kg according to the method of ASTM D1238. (X-ii) The graft amount of at least one polar compound selected from unsaturated carboxylic acids and derivatives thereof is in the range of 0.1 to 3% by mass.

4. 2. The polyamide composition according to claim 1, characterized in that the polyamide (P) is an aliphatic polyamide.

5. 2. The polyamide composition according to claim 1, wherein the polyamide (P) is one or more selected from the group consisting of nylon 6 and nylon 6,6.

6. A molded article comprising the polyamide composition according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • Polyamide composition having good fluidity

    JP2000345031A

  • Adhesive ethylene copolymer resin composition and laminate using the same

    JP2005139467A

  • Molded article from fiber-reinforced thermoplastic resin

    JP2008095066A

  • Manufacturing method of polyamide resin molded article

    JP2011148267A

  • Polyamide resin composition, and molded body of the same

    JP2019035030A